Africa RISING Baseline Evaluation Survey (ARBES) report for Ghana - Tinonin, C.; Azzarri, Carlo; Haile, Beliyou; Comanescu, M.; Roberts, C.; Signorelli, S. (International Food Policy Research Institute, 2016)
The International Food Policy Research Institute (IFPRI) leads an associated project on Monitoring and Evaluation (M&E) of AR activities. As part of the evaluation efforts of the AR program in three regions of northern Ghana (i.e. Northern, Upper West and Upper East), the M&E Team at IFPRI has contracted Pan African Field Services Limited (Panafields) to conduct the Ghana Africa RISING Evaluation Survey (GARBES), which has the primary objective of collecting highly credible and unbiased baseline data to evaluate the effectiveness of AR’s activities. In particular, the main development hypothesis that GARBES aims to test is whether AR interventions, in the form of sustainable intensification of agricultural practices, lead to an increase in agricultural productivity, income and welfare indicators (both monetary as well as non-monetary). The collected evidence on the overall effectiveness and on the specific causal pathways will also allow to draw conclusions on whether and how to scale up the program in the future.